The Effects of Environmental Physical Factors of Anthropogenic Origin on the Norway Maple (Acer Platanoides L.) in the Urban Forest of the City - Вергелес, Ю. І.; Галетич, І. К.; Данова, К. В.; Задорожний, К. М; Решетченко, А. І.; Рибалка, І. О. (Man and Environment. Issues of Neoecology)
Purpose. The impact of noise and electromagnetic fields anthropogenic origin on the state model species of trees maple. Methods. Field, biometrics, statistics. Results. Tree health effects of the Norway Maple (Acer platanoides L.) in urban forest were studied on 13 sample plots within 4 different Urban Vegetation Zones (UVZs) in summer of 2016 in the city of Kharrkiv, Ukraine. In each UVZ tree plots were selected at the distances of 10, 30 and 100 m from linear sources of urban traffic noise and power lines. The Principal Component Analysis revealed a strong positive correlation between deterioration of the tree health and increased noise levels. Conclusions. However, the noise factor cannot be considered as a principal one but a such that influences the tree health together with a complex of other anthropogenic factors of which the most significant are the percentage of artificial ground pavements, soil conditions and soil sealing.